Sustainable Development, Networks, Financial Inclusion, and Market Competitiveness: A Holistic View of Indonesian MSMEs - D. Iwan Riswandi; Arie Fitria (IPM2KPE, 2024)
This research aims to analyze the influence of financial inclusion policies, network features and sustainable development strategies on the performance and market competitiveness of Micro, Small and Medium Enterprises (MSMEs) in Indonesia. The research was conducted using a quantitative approach involving 325 MSMEs from various industrial sectors. The analytical method used is Partial Least Squares (PLS) in Structural Equation Modeling (SEM) to test the correlation between variables. The research results show that there is a significant positive correlation between market competitiveness, financial inclusion, network features, sustainable development practices and the performance of MSME companies. The conclusion is that sustainable development practices, involvement in business networks, and access to financial services have a significant positive impact on market competitiveness and performance of MSME companies. The implication of these findings is the importance of integrating sustainability programs, encouraging business collaboration, and expanding financial inclusion to support sustainable growth and competitiveness of MSMEs in Indonesia. Keywords: Market Competitiveness, Network Characteristics, Financial Inclusion, Sustainable Development, MSMEs This research aims to analyze the influence of financial inclusion policies, network features and sustainable development strategies on the performance and market competitiveness of Micro, Small and Medium Enterprises (MSMEs) in Indonesia. The research was conducted using a quantitative approach involving 325 MSMEs from various industrial sectors. The analytical method used is Partial Least Squares (PLS) in Structural Equation Modeling (SEM) to test the correlation between variables. The research results show that there is a significant positive correlation between market competitiveness, financial inclusion, network features, sustainable development practices and the performance of MSME companies. The conclusion is that sustainable development practices, involvement in business networks, and access to financial services have a significant positive impact on market competitiveness and performance of MSME companies. The implication of these findings is the importance of integrating sustainability programs, encouraging business collaboration, and expanding financial inclusion to support sustainable growth and competitiveness of MSMEs in Indonesia. Keywords: Market Competitiveness, Network Characteristics, Financial Inclusion, Sustainable Development, MSMEs